2021
DOI: 10.3390/nu13124551
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Cancer Patients Receiving Enteral Nutrition: A Systematic Review of Randomized Controlled Trials

Abstract: Most studies confirm the beneficial effects of enteral nutrition on the quality of life, but some studies indicate an inverse association and its detrimental impacts. However, there are insufficient data on the effects of enteral nutrition on the quality of life of cancer patients. This systematic review aimed to describe the influence of applied enteral nutrition on the quality of life of cancer patients, based on the results of randomized controlled trials. It was registered in the PROSPERO database (CRD4202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Results showed that glutamine could significantly eliminate the maximal mucositis grade and pain score at Weeks 4, 5, and 6. 15 However, these results are somewhat in conflict with the results of the study done by Gliwska et al, 16 which determine whether glutamine supplementation is effective in reducing the incidence and severity of radiation-or chemoradiation-induced mucositis and dermatitis in head and neck cancer patients. The incidence and severity of oral mucositis in the sixth week did not exhibit statistically significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Results showed that glutamine could significantly eliminate the maximal mucositis grade and pain score at Weeks 4, 5, and 6. 15 However, these results are somewhat in conflict with the results of the study done by Gliwska et al, 16 which determine whether glutamine supplementation is effective in reducing the incidence and severity of radiation-or chemoradiation-induced mucositis and dermatitis in head and neck cancer patients. The incidence and severity of oral mucositis in the sixth week did not exhibit statistically significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 90%
“…With this in mind, the European Society for Nutrition and Metabolism guideline states that early screening and assurance about patients' nutritional interventions is crucial in overcoming cancer‐related malnutrition 15 . Prevention and treatment of oral mucositis are essential as malnutrition affects the efficacy of cancer treatment, prognosis, hospitalization period, and the patient's quality of life 16,19 . Early detection and treatment of oral SCC will contribute to a complete cure and 5‐year survival in 85% 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the literature has indicated that impaired nutritional status may affect tolerance to surgery and the prognosis of patients with various types of cancer. [3][4][5] In this context, the Controlling Nutritional Status (CONUT) score was developed by Ignacio de Ulíbarri et al [6] for screening the preoperative nutritional status. This index was calculated based on the preoperative serum albumin concentration, total peripheral blood lymphocyte count, and total cholesterol concentration (Supplementary Table S1, http://links.lww.com/CURRUROL/A46).…”
Section: Introductionmentioning
confidence: 99%
“…For patients with advanced malignant tumors or after digestive tract reconstruction, enteral nutrition is crucial for clinical antitumor treatment (1,2), not only because of convenience and efficacy, but also reducing the probability of enterogenous infection and further improving the stress and immune function of patients (3)(4)(5). Patients with advanced malignant tumors can have widely dispersed metastases and different degrees of organ invasion, often resulting in an intestinal obstruction that is difficult to pass with a gastroscopically guided nasoenteric tube.…”
Section: Introductionmentioning
confidence: 99%